Optimizing PoS agent banking for inclusive rural economies: - Ishmael Obaeko IWARA (Academic Finance)
Purpose: This paper explores the impact of Point-of-Sale (PoS) agent banking on streamlining digital and cash transactions, emphasizing its potential to alleviate financial exclusion in rural South African communities while addressing inherent challenges.